EFEKTIVITAS MODEL REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA: SEBUAH SYSTEMATIC LITERATURE REVIEW - Hamdiyah, Siti; Pujiastuti, Heni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the Realistic MathematicsEducation (RME) approach in enhancing students' ability to represent mathematics,which remains low in conventional learning. Employing PRISMA 2020-based Systematic Literature Review (SLR), literature search was conducted onGoogle Scholar (2013-2025) using keywords RME and mathematicalrepresentation, yielding 14 high-quality empirical articles (quasi-experiments,classroom action research) from 420 initial records. Thematic-content analysisand meta-descriptive synthesis demonstrate RME consistently improves verbal,visual, and symbolic representation abilities (effect size 0,65-1,2 SD), outperformingconventional/STAD approaches across elementary-secondary levels. Superiority isevident through real-world contexts and concrete media utilization. These findingsconfirm RME as an effective pedagogical solution for mathematical literacy teachertraining, and RME-based module development is recommended.